State of Science: Bridging the Science‐Practice Gap in Aging, Dementia and Mental Health. (16th April 2018) - Callahan, Christopher M.; Bateman, Daniel R.; Wang, Sophia; Boustani, Malaz A.
Abstract : The workforce available to care for older adults has not kept pace with the need. In response to workforce limitations and the growing complexity of healthcare, scientists have tested new models of care that redesign clinical practice. This article describes why new models of care in aging, dementia, and mental health diffuse inadequately into the healthcare systems and communities where they might benefit older adults. We review a general framework for the diffusion of innovations and highlight the importance of other features of innovations that deter or facilitate diffusion. Although scientists often focus on generating evidence‐based innovations, end‐users apply their own criteria to determine an innovation's value. In 1962, Rogers suggested six features of an innovation that facilitate or deter diffusion suggested: relative advantage, compatibility with the existing environment, ease or difficulty of implementation, trial‐ability or ability to "test drive", adaptability, and observed effectiveness. We describe examples of models of care in aging, dementia and mental health that enjoy a modicum of diffusion into practice and place the features of these models in the context of deterrents and facilitators for diffusion. Developers of models of care in aging, dementia, and mental health typically fail to incorporate the complexities of health systems, the barriers to diffusion, and the role of emotion into design considerations of new models. We describe agile implementation as a strategy to facilitate the speed and scale of diffusion in the setting of complex adaptive systems, social networks, and dynamic macroenvironments.